Content and face validity and feasibility of 5 candidate instruments for psoriatic arthritis randomized controlled trials: The PsA OMERACT Core Set Workshop at the GRAPPA 2017 Annual Meeting - Holland, R; Tillett, W; Ogdie, A; Leung, Y; Gladman, D; Callis Duffin, K; Coates, L; Mease, P; Eder, L; Strand, V; Elmamoun, M; Højgaard, P; et al. (Journal of Rheumatology, 2018)
The Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA)–Outcome Measures in Rheumatology (OMERACT) Psoriatic Arthritis (PsA) Core Set working group is in the process of selecting core instruments for PsA clinical trials. During a 2-h workshop and breakout group discussions at the GRAPPA 2017 annual meeting in Amsterdam, the Netherlands, participants discussed the first set of candidate instruments to be taken through the OMERACT Filter 2.1 instrument selection process: 66/68 swollen/tender joint count (66/68JC), Spondyloarthritis Consortium of Canada (SPARCC) enthesitis index, patient’s global assessment (GRAPPA and OMERACT formulations), Health Assessment Questionnaire–Disability Index (HAQ-DI), Psoriatic Arthritis Impact of Disease (PsAID) questionnaires 9 and 12, and Functional Assessment of Chronic Illness Therapy (FACIT) Fatigue. Based on the assessment of domain match (content and face validity) and feasibility according to the OMERACT instrument selection criteria, the working group recommends continuing with appraisal of construct validity and discrimination for 66/68JC, SPARCC, PsAID 9 and 12, HAQ-DI, and FACIT-Fatigue. In addition, it recommends repeating the OMERACT Filter 2.1 process for patient global instruments because of insufficient votes. Additional sets of candidate instruments for the PsA core instrument set will be evaluated in a similar process.